Slew rate control of a 600 V 55 mΩ GaN cascode - Endruschat, Achim; Heckel, Thomas; Reiner, Richard; Waltereit, Patrick; Quay, Rüdiger; Ambacher, Oliver; März, Martin; Eckardt, Bernd; Frey, Lothar (4th IEEE Workshop on Wide Bandgap Power Devices and Applications, WiPDA 2016, 2016)
This paper presents a 600 V, 55 m Omega GaN cascode with slew rate control. The time constants of cascodes which determine the switching speed are analyzed, discussed and verified by time domain simulations. Clamped inductive switching measurements of commercial and a custom-built GaN cascodes prove the applicability of the switching speed control mechanisms with additional passive components. The gathered experiences are applied to a custom-built modular cascode, which shows simple switching speed controllability by utilizing a standard gate driv
Keywords: Cascode; Gallium nitride; HEMT; MOSFET; Pulse measurements; Semiconductor device measurement